Teaching English Vocabulary to Young Learners: An ESL Approach with Scouting Themes - Wiwiek Meisuri; Aqila Adha Br Tanjung; Karina Salsabila Hasim; Martha Carolina Sinaga; Reinhard Panjaitan; Shinta Martha Delima Lumban Gao (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Teaching English vocabulary to young learners requires engaging and structured instructional methods to enhance retention and practical usage. This study explores the effectiveness of Thematic-Based Learning (TBL) in teaching scouting-related vocabulary to elementary school students. Over five teaching sessions, students were introduced to scouting objects, ranks, nature words, simple commands, and camping activities through structured activities such as verbal repetition, Q&A exercises, and board-based word matching tasks. The study focused on three key aspects: (1) vocabulary retention, (2) vocabulary usage in communication, and (3) student motivation and engagement. Findings indicate that students retained words more effectively when they were concrete and visually relatable, whereas abstract terms and multi-word expressions were more challenging to remember. Students demonstrated strong word recognition but struggled to use the vocabulary in full sentences, highlighting the need for additional communicative reinforcement. Motivation levels varied, with higher engagement observed in familiar, action-based topics, whereas more abstract vocabulary led to lower participation and classroom management challenges. This research confirms that Thematic-Based Learning is a valuable approach for young learners in ESL vocabulary instruction, but additional strategies—such as structured speaking exercises and extended reinforcement activities—are necessary to bridge the gap between memorization and practical application. The findings contribute to the ongoing discussion on effective ESL vocabulary teaching strategies and suggest avenues for future studies to explore more interactive and multimodal approaches to vocabulary acquisition.